Management Information System Web Based Visitor Data Center on PT. Media Nusantara Citra. Tbk (MNC Media) - Ishak Kholil; Dede Unggara (Universitas Islam Kuantan Singingi, 2023)
Information technology is currently developing very quickly. Hardware and software are tools created to facilitate human work. PT Media Nusantara Citra is a company engaged in the field of information media; of course, it is very dependent on information systems in its operations. This is to provide support and make it easy to make decisions. And one of them that is still managed manually is the management of visitor activity data in the PT Media Nusantara Citra data center. Departing from this, the author chose the theme of the web-based Visitor Management Information System at PT Media Nusantara Citra, what is currently happening in the management of visitor data in the data center is the inaccuracy of visitor data every day, and the lack of efficiency in document recording and storage, starting from recording data processing of incoming visitor activities, recording various types of visitor data activities that have been completed, to preparing reports on incoming visitor data activities and various types of visitor activities that have been completed, the authors propose a web-based Visitor Management Information System to be a solution to some of the above, and information system-based visitor data management is expected to increase effectiveness and efficiency in data management.